A comparison on internal structures of a leaf in Dryas octopetala between populations growing in the Arctic and mid-latitude alpine II - Wada, Naoya; Murai, Moeka; Shima, Akane; Tamaoki, Daisuke; Karahara, Ichirou; Sekikawa, Seikoh; Cooper, Elisabeth J.; Uchida, Masaki (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OB] Polar biology, Wed. 5 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object